2022
DOI: 10.1021/acs.energyfuels.2c00445
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanoparticles in Stimulation: A Review

Abstract: Oil well stimulation treatments have been employed to improve the productivity index, either by imposing a negative skin effect through hydraulic fracturing or by reducing a positive skin effect using matrix acidizing. The commonly used stimulation fluids are polymer-based, viscoelastic surfactant-based, emulsion (oil)-based, and foam-based. The stability and performance efficiency of the stimulation fluids under harsh conditions of high temperature and high pressures have remained a critical factor. Thus, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 179 publications
(360 reference statements)
0
4
0
Order By: Relevance
“…Moreover, compared with the conventional systems, the addition of NPs improved the proppant-suspension ability (Figure ). Due to the pseudocross-linking of NPs and WLMs, the elastic modulus of the VES fluid is increased and its suspension performance is enhanced. , A follow-up study by Huang et al also demonstrated the wall-building performance of the NP-based systems, and the retained permeability of the system was 100%. Liu et al prepared a silica nanoparticle-reinforced CO 2 -sensitive fracturing fluid system.…”
Section: High-temperature-resistant Ves Fracturing Fluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, compared with the conventional systems, the addition of NPs improved the proppant-suspension ability (Figure ). Due to the pseudocross-linking of NPs and WLMs, the elastic modulus of the VES fluid is increased and its suspension performance is enhanced. , A follow-up study by Huang et al also demonstrated the wall-building performance of the NP-based systems, and the retained permeability of the system was 100%. Liu et al prepared a silica nanoparticle-reinforced CO 2 -sensitive fracturing fluid system.…”
Section: High-temperature-resistant Ves Fracturing Fluidsmentioning
confidence: 99%
“…It is worth noting that the effects of exposure to NPs on human health and the environment have not been fully documented. 293,331 Due to their extremely small size, the NPs may easily enter organisms and have adverse effects on them. In the future, more efforts should be made to utilize natural nanomaterials, such as lignin nanoparticles.…”
Section: Counterion Salt Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other nanoparticles were evaluated for their efficacies in enhancing the quality of the fracturing fluids. They were found to have applications as cross-linking agents as well as gel breakers, leak-off control additives, rheology modifiers, foam stabilizers, proppant surface modifiers, and emulsion stabilizers in different types of stimulation fluids [154]. However, despite the exceptional performance displayed in the laboratories, their field application is still limited.…”
Section: Silica Nanoparticles (Snp)mentioning
confidence: 99%
“…Nanomaterials have attracted extensive attention in recent years. Nanotechnology has been used to enhance oil recovery and to improve drilling fluid properties and depressurization and injection-augmenting in water injection wells to achieve more efficient development. The application of nanoinjection-augmenting technology in oilfields has achieved excellent development effects. However, this technology has not been widely promoted, and most reports are limited to laboratory studies.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%